Exploring the molecular mechanisms of reactions at surfaces - Gonzalez Perez, S. (2017)
The study of the molecular mechanism of chemical reactions occurring at solid surfaces is of primary importance to understand heterogeneous catalysis from a microscopic point of view. The present paper reviews the state of the art methods of electronic structure and the surface models currently used in this type of studies by making use of three different examples. Those are the decomposition of azomethane on Pt( 111), the study of the different selectivity of Cu( 111) and Ag( 111) towards ethene partial oxidation and the comparative study of NO dissociation on Rh( 111) and bimetallic RhCu( 111) surfaces. These examples illustrate the power of the electronic structure computational approaches to predict the structure and stability of different intermediates and to unravel the molecular mechanism of these surface reactions.